Efektivitas Berbagai Dosis Rekashet untuk Menurunkan Kesadahan Air Sumur Gali di Desa Jimbing, Kalikotes, Klaten - Novi Astrini; Haryono hary; Bambang Suwerda (Poltekkes Kemenkes Yogyakarta, 2016)
Jimbung village is a limestone hilly or mountaineous area. This condition causes the dug well water contain lime or have high hardness. The use of hard water continuously can raise several problems, among others: health disorder such as kidney stones disease, economical problem because of the increase use of soaps, and technical problems such as crust on household appliances. The purpose of this research was to know whether the addition of various resindoses affect the decrease of water hardness of the well water. The type of the research was an experiment with pre-post test with control group design. In the control group, the water sample were boiled, meanwhile in the treatment group, in addition to the boiling, Rekashet were also added to the sample water. Rekashet is an abbreviation for cation resin sachet, i.e. resin which is packed practically in a sachet like a tea bag. Data from water hardness measurement between pre-test and post-test were analyzed by using paired sample t-test at 95 % significance level. The results show that p-value obtained for the control group was 0,006; Rekashet dose of 2 gr/L was 0,001; Rekashet dose of 3 gr/L was 0,004; Rekashet dose of 4 gr/L was <0,001; Rekashetdose of 5 gr/L was 0,002; and Rekashet dose of 6 gr/L was 0,004. To conclude, various doses of Rekashet addition influence the decrease of water hardness from water wells in Jimbung Village.